Synchrony Drives Motor Cortex Beta Bursting, Waveform Dynamics, and Phase-Amplitude Coupling in Parkinson's Disease - O'Keeffe, Andrew B. (J Neurosci, 2020)
Several lines of inquiry have separately identified beta oscillations, synchrony, waveform shape, and phase-amplitude coupling as important but sometimes inconsistent factors in the pathophysiology of Parkinson's disease. What has so far been lacking is a means by which these neurophysiological parameters are interrelated and how they relate to clinical symptomatology. To clarify the relationship among oscillatory power, bursting, synchrony, and phase-amplitude coupling, we recorded local field potentials/electrocorticography from hand motor and premotor cortical area in human subjects with c (N = 10) and Parkinson's disease (N = 22) during deep brain stimulator implantation surgery (14 females, 18 males). We show that motor cortical high beta oscillations in Parkinson's disease demonstrate increased burst durations relative to essential tremor patients. Notably, increased corticocortical synchrony between primary motor and premotor cortices precedes motor high beta bursts, suggesting a possible causal relationship between corticocortical synchrony and localized increases in beta power. We further show that high beta bursts are associated with significant changes in waveform shape and that beta-encoded phase-amplitude coupling is more evident during periods of high beta bursting. These findings reveal a deeper structure to the pathologic changes identified in the neurophysiology of Parkinson's disease, suggesting mechanisms by which the treatment may be enhanced using targeted network synchrony disruption approaches. SIGNIFICANCE STATEMENT Understanding Parkinson's disease pathophysiology is crucial for optimizing symptom management. Present inconsistencies in the literature may be explained by temporal transients in neural signals driven by transient fluctuations in network synchrony. Synchrony may also act as a unifying phenomenon for the pathophysiological observations reported in Parkinson's disease. Here, simultaneous recordings from motor cortices show that increases in network beta synchrony anticipate episodes of beta bursting. We furthermore identify beta bursting as being associated with changes in waveform shape and increases in phase-amplitude coupling. Our results identify network synchrony as a driver of various pathophysiological observations reported in the literature and account for inconsistencies in the literature by virtue of the temporally variable nature of the phenomenon.